The monetary value of cultural goods: a contingent valuation study of the municipal supply of cultural goods in Lueneburg, Germany - Anne-Kathrin Last (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
This paper aims to determine if the contingent valuation method (CVM) can provide valid results useful in policy-making. This will be investigated by using a CV study that captures the willingness to pay (WTP) for the municipal cultural supply in Lueneburg, Germany. In contrast to previous CV studies that included a wide range of descriptive statistics, the empirical analysis of the current study focuses on multivariate analysis to explore the factors associated with the WTP ...
Keywords: H44; Z10; 330; Kulturgut; Willingness to pay; Kulturpolitik; Lüneburg